Case of Candida auris Identified From the External Ear Canal of a Healthy Minnesota Outpatient With Travel to South Korea. (October 2020) - Pattee, Brittany; Tourdot, Laura; Beaudoin, Amanda; Dale, Jennifer; Fischer, Jill; Lovett, Leslie; Walters, Jacy; Alpern, Jonathan; Ellyson, Keely
Abstract : Background: Candida auris is a globally emerging, multidrug-resistant fungal pathogen that causes healthcare-associated outbreaks and can be misidentified in clinical laboratories. Most US C. auris cases occur in hospitalized or long-term care patients with underlying medical conditions. Also, 4 global phylogenetic C. auris clades largely cluster geographically. Receiving health care abroad is a risk factor for US C. auris cases. In December 2019, the Minnesota Department of Health (MDH) confirmed Minnesota's first C. auris case, isolated from the external ear canal of a healthy young adult outpatient with right-sided otitis externa. We describe the investigation and response for this uncommon US presentation of C. auris . Methods: The MDH initiated mandatory reporting and submission of confirmed or possible C. auris isolates in August 2019. The MDH Public Health Laboratory (MDH-PHL) confirmed C. auris by MALDI-TOF (Bruker) from an isolate submitted by a hospital laboratory as C. duobushaemulonii to rule out C. auris . The MDH-PHL performed broth microdilution antifungal susceptibility testing (AFST). The CDC Mycotics Diseases Branch laboratory performed whole-genome sequencing (WGS). The MDH epidemiologists obtained a patient history through interviews with healthcare staff and the patient, and they collected environmental samples from otoscopes. The MDH-PHL tested environmental samples by C. auris RT-PCR and culture. The MDH recommended disinfection of examination rooms and otoscopes and 3 months of C. auris surveillance for patients evaluated with otoscopes who later returned with otic inflammation. Swabs from the patient's axilla, groin, and external ear canals were tested for C. auris by PCR at the MDH-PHL. Results: The patient reported recurrent right ear infections in 2016 during a 16-month visit to South Korea, with treatment in multiple ENT clinics. December 2019 otitis resolved after treatment with oral amoxicillin/clavulanate and otic ciprofloxacin/dexamethasone. AFST showed resistance to fluconozale and susceptibility to 8 antifungals, including echinocandins. WGS placed the isolate in the East Asian clade, indicating similarity to isolates from South Korea and Japan. Environmental cultures were negative. The asymptomatic left ear was colonized with C. auris ; other sites were negative. As of January29, 2020, no additional cases were detected. Conclusions: We identified prolonged colonization of C. auris in the external ear canals of a healthy patient. WGS and travel in South Korea, including ENT clinic exposure, provide strong evidence of C. auris acquisition in South Korea. No spread has been reported in Minnesota. Deliberate communication with clinical laboratories regarding ruling out C. auris was key to case discovery. Clinicians should be aware of C. auris epidemiology, including healthcare exposure abroad, particularly in young, healthy patients. Funding: None Disclosures: None